1) а) с^4 × с^7 : с^9 = с^(4+7-9) = с^2
б) (а^4)^3 × а = а^(4×3+1) = а^13
в) (-2х)^4 = (-2)^4 × х^4 = 16х^4
г) -2,5а^-2 в^3 × 4а^7в^-5 = -10 а^(-2+7) в^(3-5) = -10 а^5 в^-2
2) а) (2х^2 - 3х) - (5х - х^2) = 2х^2 - 3х - 5х + х^2 = 3х^2 - 8х
б) -3х (2х - 1) = -6х^2 + 3х
в) (3 - у^2) × (у - 4) = 3у - 12 - у^3 + 4у^2
3) х^2 - (х + 4) × (х - 4) = 2х
х^2 - (х^2 - 4х + 4х - 16) = 2х
х^2 - х^2 + 16 - 2х = 0
16 = 2х
16 : 2 = х
х = 8
4) (х - 2)^2 + 4х = х^2 - 4х + 4 + 4х = х^2 + 4
Если х = - 1/2 , то (-1/2)^2 + 4 = 0,5^2 + 4 = 0,25 + 4 = 4,25